Die Prognose von Spielausgängen in der Fußball-Bundesliga - Stefan Niermann (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2001)
– In this paper models for the prediction of matches in the German Soccer Bundesliga are estimated. In a frst step the expected difference of the number of goals is estimated on the basis of estimated abilities of the teams. Here, a focus lies on the necessity of robust parameter estimation. In a second step the probabilities for home team wins/losses and ties are estimated using a Bayesian updating procedure.
Keywords: 330; Fußball-Bundesliga; Prognose; Bayesian Updating